Respuesta :
Answer:
As the lengths of the two sides is equal. i.e. WY = WX [tex]=\sqrt{74}[/tex]. Therefore, the triangle WXY is an isosceles triangle.
Step-by-step explanation:
Considering the triangle with the vertices
- W(-10, 4)
- X(-3, -1)
- Y(-5, 11)
The distance between the W(-10, 4) and Y(-5, 11) is the length of the side WY.
So,
[tex]\mathrm{Compute\:the\:distance\:between\:}\left(x_1,\:y_1\right),\:\left(x_2,\:y_2\right):\quad \sqrt{\left(x_2-x_1\right)^2+\left(y_2-y_1\right)^2}[/tex]
[tex]\mathrm{The\:distance\:between\:}\left(-10,\:4\right)\mathrm{\:and\:}\left(-5,\:11\right)\mathrm{\:is\:}[/tex]
[tex]=\sqrt{\left(-5-\left(-10\right)\right)^2+\left(11-4\right)^2}[/tex]
[tex]=\sqrt{\left(-5+10\right)^2+\left(11-4\right)^2}[/tex]
[tex]=\sqrt{5^2+7^2}[/tex]
[tex]=\sqrt{5^2+7^2}[/tex]
[tex]=\sqrt{74}[/tex]
So, the length of the side WY [tex]=\sqrt{74}[/tex].
Similarly,
The distance between the W(-10, 4) and X(-3, -1) is the length of the side WX.
[tex]\mathrm{The\:distance\:between\:}\left(-10,\:4\right)\mathrm{\:and\:}\left(-3,\:-1\right)\mathrm{\:is\:}[/tex]
[tex]=\sqrt{\left(-3-\left(-10\right)\right)^2+\left(-1-4\right)^2}[/tex]
[tex]=\sqrt{\left(-3+10\right)^2+\left(-1-4\right)^2}[/tex]
[tex]=\sqrt{49+5^2}[/tex]
[tex]=\sqrt{49+25}[/tex]
[tex]=\sqrt{74}[/tex]
So, the length of the side WX [tex]=\sqrt{74}[/tex].
As the lengths of the two sides is equal. i.e. WY = WX [tex]=\sqrt{74}[/tex]. Therefore, the triangle WXY is an isosceles triangle.